Improvement in lithium-ion transport performance of cathodes by PEGDA-based solid-state electrolyte - Zhang, Yongquan; Zhu, Baoshan; Chi, Qingguo; Gao, Hongchang; Zhang, Changhai; Zhang, Tiandong; Zhu, Kai; Cao, Dianxue (Frontiers in Energy Research, 2022)
The transport performance of lithium-ion affects the rate performance of cathode at different current densities. The poor interface contact between solid electrolyte and cathode makes it difficult to transport lithium-ion. Adding solid electrolyte into the cathode material can improve the lithium-ion transport. In this paper, we prepared some cathodes with different doping ratios, including two common cathode materials (LiFePO4 and NCM811), and tested their rate and long cycle performance. LFP-10 still has a specific discharge capacity of 79.75 mAh g-1 at 5C, and the Li+ diffusion coefficient of LFP-10 is 4.91×10-13 cm-2 s-1, which is about 13.4 times higher than the pure LiFePO4 sample. The rate performance of all solid-state battery has also been improved, and there is still more than 100 mAh g-1 capacity reserved at 60 ℃ and 2C current density. This shows that the introduction of PEGDA-based solid electrolyte can significantly improve the Li+ transport of the cathode, and the composite cathode also provides support for the future application of all solid-state batteries.